Venture capital financing and green patenting - Andrea Bellucci; Serena Fatica; Aliki Georgakaki; Gianluca Gucciardi; Simon Letout; Francesco Pasimeni (European Commission, 2021)
This paper explores the role of green innovation in attracting venture capital (VC) financing. We use a unique dataset that matches information on VC transactions, companies' balance sheet variables and data on patented innovation at the firm level over the period 2008-2017. Taking advance of a novel granular definition of green innovative activities that tracks patents at the firm level, we show that green innovators are more likely to receive VC funding than firms without green patents. Likewise, a larger share of green vs. non-green patents in a firm's portfolio increases the probability of receiving VC finance. Robustness checks and extensions tackling several dimensions of heterogeneity corroborate the view that green patenting is an important driver of VC funding.
Keywords: G24; M13; M21; O35; Q55; 330; Venture capital; Green ventures; Patents; Green technology